Impact of pollutants on aneuploidy in the Pacific oyster, Crassostrea gigas - Bouilly, Karine; Leitao, Alexandra; Mccombie, Helen; Miramand, Pierre; Lapegue, Sylvie (III Congrès International des Sociétés Européennes de Malacologie, La Rochelle, 24-27 huin 2003, 101-102 (Richard G. ed.), 2003)
Aneuploidy is the alteration of the normal diploid chromosome number. In the Pacifie oyster, Crassastrea gigas, hypodiploid cells have regularly been reported as have a negative correlation between this phenomenon and growth and evidence for a genetic basis. We previously demonstrated a positive relationship between a pollutant, atrazine, and aneuploidy in Crassastrea gigas adults and juveniles. To evaluate the persistence of this impact, the present study focused on a sample of the same juveniles previously exposed to different atrazine treatments (0.0 1 mg/l which represents a peak value found in a polluted environment and 0.1 mg/l) for three and a half months. Then, we evaluated them for aneuploidy after another two and a half months in non polluted conditions. Their aneuploidy level remained significantly different between the treatments applied. In addition, our study examined the offspring of the adult population previously treated and found that these offspring exhibited significantly higher aneuploidy levels when the parents had been exposed to atrazine. Recently, adult oysters contaminated by another pollutant, cadmium (50 and 500 ng/l), also showed higher aneuploidy levels than the contrQls. These results demonstrate the persistence of atrazine impact in time within and between generations and c1early show that environmental factors can influence aneuploidy in Pacifie oysters.